Effect of Gama rays on the protein and gaseous content of seeds, parts and calves of sun flower plants Helianthus annus L. - Abdullah Al-nuaimi; Taghreed Al-Akeedi (College of Education for Pure Sciences, 2007)
This study has include the exposure of the seeds, explants and callus of Helianthus annus L. by gamma rays, with the doses (0.3, 0.7, 1.1, 1.3, 1.5) kilorad, this resulted increasing protein content in radiant peeled seeds with all radiant doses, and in radiant complete seeds, only four radiant doses (0.3, 1.1, 1.3, 1.5) kilorad, also the leaves and stems callus that produced from radiant seed plants , also in all radiant callus. At dose ( 1.3) kilorad initiative seeds has recorded best percents of oil in both leaves and hypocotyls that produced it, also shown that highest present of oil in both radiant hypocotyls and leaves callus. Oil percent in callus produced by radiant explants was in som~ dose higher than the control or equal .